Weeds Assessment di Perkebunan Kelapa Sawit Lahan Gambut - Edy Syahputra; Sarbino Sarbino; Siti Dian (Fakultas Pertanian Universitas Tanjungpura, 2011)
Activity and effectiveness of insecticide mixtures (thiodicarb and triflumuron) against physics caterpillar pests Metisa plana on oil palm plantation. The objectives of this study were to evaluate the joint action of thiodicarb and triflumuron insecticides in the laboratory, and to determine their effectiveness in supressing population of M. plana in the field. The mortality bioassays were conducted by a spraying method. The results showed that the inseticide mixtures between thiodicarb and triflumuron possessed a sinergistict activity against M. plana larvae with insecticide combination index of 0.49%. Iinsecticide mixtures at a range dose of 250 - 1250 ml/ha spraying on oil palm planst effectively suppressed population of M. plana larvae.